2023
DOI: 10.1021/acsami.3c08766
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived ZnO, N Dually Doped Nanocages as an Efficient Host for Stable Li Metal Anodes

Abstract: The drastic volume expansion and dendrite growth of lithium metal anodes give rise to poor electrochemical reversibility. Herein, ZnO, N dually doped nanocages (c-ZNCC) were synthesized as the host for lithium metal anodes using the zeolitic imidazolate framework-8 (ZIF-8). The synthesis is based on a two-step core@shell evolution mechanism, which could guide lithium deposition rapidly and offer a fast lithium-ion diffusion during the cycling process. Benefiting from the unique design, the as-obtained c-ZNCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) was employed to analyze the impedance changes of the Mg-CO 2 batteries with a Mo 2 C-NDs@CNF cathode at different stages of the chargedischarge test. [56][57][58][59][60][61][62] After discharge, the cathode's charge transfer resistance experiences a substantial increase due to the formation and deposition of discharge product layer with poor conductivity on the electrode's surface (Figure 3g,h and Tables S1 and S2 (Supporting Information)). [63][64][65] Conversely, the decrease in electrode R ct (value obtained from EIS fitting using ZView) observed after charge corresponds to the decomposition of the discharge products.…”
Section: Electrochemical Performance Of Mo 2 C-nds@cnf Catalytic Cath...mentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) was employed to analyze the impedance changes of the Mg-CO 2 batteries with a Mo 2 C-NDs@CNF cathode at different stages of the chargedischarge test. [56][57][58][59][60][61][62] After discharge, the cathode's charge transfer resistance experiences a substantial increase due to the formation and deposition of discharge product layer with poor conductivity on the electrode's surface (Figure 3g,h and Tables S1 and S2 (Supporting Information)). [63][64][65] Conversely, the decrease in electrode R ct (value obtained from EIS fitting using ZView) observed after charge corresponds to the decomposition of the discharge products.…”
Section: Electrochemical Performance Of Mo 2 C-nds@cnf Catalytic Cath...mentioning
confidence: 99%
“…An anode is a polarized electrical device in the battery structure that directly influences the battery capacity and performance via its morphology and the employed content since they are responsible for storing and releasing Li + ions during the charging and discharging procedure . A variety of synthetic and natural-based materials have been introduced as anode materials so far.…”
Section: Electrospun Cellulose-based Anode Structuresmentioning
confidence: 99%
“…For decades, green chemistry, energy regeneration, and other energy issues have been a problem that all researchers have been trying to solve. Over the years, the large amount of primary energy inputs has led to a gradual increase in the proportion of global pollution, along with the depletion of nonrenewable energy problems, so there is an urgent need for secondary energy technology that can be used as a substitute. According to literature research, zinc-air batteries have great potential as a secondary energy technology because of their huge theoretical energy. Although it has great potential, the slow kinetics of the oxygen reduction and oxygen precipitation reactions during the charging and discharging process of zinc-air batteries lead to low cycle efficiency, which prevents the batteries from being used on a large scale. Pt-based noble metals are considered to be the ideal catalysts for zinc-air batteries, but due to their scarcity, they are not available for large-scale applications due to their high cost. Therefore, according to the literature, it was found that in recent years, many researchers have done a lot of work on the nonprecious metal catalysts used, such as doped transition metal oxides, synthesized MOFs and COFs, carbon-based materials containing metals, and so on, in place of precious metals. Although a lot of beautiful work has been done and quite high performance has been shown, it is still not up to the desired level.…”
Section: Introductionmentioning
confidence: 99%